Cutmarked bones from Pliocene archaeological sites at Gona, Afar, Ethiopia: implications for the function of the world's oldest stone tools - Dominguez-Rodrigo, Manuel; Pickering, Travis Rayne; Semaw, Sileshi; Rogers, Michael J (Journal of Human Evolution, 2005)
Newly recorded archaeological sites at Gona (Afar, Ethiopia) preserve both stone tools and faunal remains. These sites have also yielded the largest sample of cutmarked bones known from the time interval 2.58-2.1 million years ago (Ma). Most of the cutmarks on the Gona fauna possess obvious macroscopic (e.g., deep V-shaped cross-sections) and microscopic (e.g., internal microstriations, Herzian cones, shoulder effects) features that allow us to identify them confidently as instances of stone tool-imparted damage caused by hominid butchery. In addition, preliminary observations of the anatomical placement of cutmarks on several of the recovered bone specimens suggest that Gona hominids may have eviscerated carcasses and defleshed the fully muscled upper and intermediate limb bones of ungulates-activities that further suggest that Late Pliocene hominids may have gained early access to large mammal carcasses. These observations support the hypothesis that the earliest stone artifacts functioned primarily as butchery tools and also imply that hunting and/or aggressive scavenging of large ungulate carcasses may have been part of the behavioral repertoire of hominids by c. 2.5 Ma, although a larger sample of cutmarked bone specimens is necessary to support the latter inference. (c) 2004 Elsevier Ltd. All rights reserved.
Keywords: Africa; Carcass; Cutmarks; Defleshing/filleting; East Africa; Eastern Hemisphere; Ethiopia; Evisceration; Gona; Hominidae; Hominids; Mammalia; Pliocene; Stone tools; Sub-Saharan Africa; Ungulata; World; archaeological evidence; dept.ant; hominid; peer-reviewed; tool use

Raw material selectivity of the earliest stone toolmakers at Gona, Afar, Ethiopia - Stout, Dietrich; Quade, Jay; Semaw, Sileshi; Rogers, Michael J.; Levin, Naomi E. (Journal of Human Evolution, 2005)
Published evidence of Oldowan stone exploitation generally supports the conclusion that patterns of raw material use mere determined by local availability. This is contradicted by the results of systematic studies of raw material availability and use among the earliest known archaeological sites from Gona, Afar, Ethiopia. Artifact assemblages from six Pliocene archaeological sites were compared with six random cobble samples taken from associated conglomerates that record pene-contemporaneous raw material availability. Artifacts and cobbles were evaluated according to four variables intended to capture major elements of material quality: rock type, phenocryst percentage, average phenocryst size, and groundmass texture. Analyses of these variables provide evidence of hominid selectivity for raw material quality. These results demonstrate that raw material selectivity was a potential component of Oldowan technological organization from its earliest appearance and document a level of technological sophistication that is not always attributed to Pliocene hominids. (c) 2004 Elsevier Ltd. All rights reserved.
Keywords: Africa; Cognition; East Africa; Eastern Hemisphere; Ethiopia; Gona; Hominidae; Lithic technology; Oldowan; Pene; Pliocene; Raw materials; Sub-Saharan Africa; World; dept.ant; human activity; lithic fragment; peer-reviewed

Early Pliocene hominids from Gona, Ethiopia. - Semaw, Sileshi; Simpson, Scott; Quade, Jay; Renne, Paul; Butler, Robert; McIntosh, William; Levin, Naomi; Dominguez-Rodrigo, Manuel; Rogers, Michael (Nature, 2005)
Comparative biomolecular studies suggest that the last common ancestor of humans and chimpanzees, our closest living relatives, lived during the Late Miocene-Early Pliocene 1,2. Fossil evidence of Late Miocene-Early Pliocene hominid evolution is rare and limited to a few sites in Ethiopia 3-5, Kenya 6 and Chad 7. Here we report new Early Pliocene hominid discoveries and their palaeoenvironmental context from the fossiliferous deposits of As Duma, Gona Western Margin (GWM), Afar, Ethiopia. The hominid dental anatomy (occlusal enamel thickness, absolute and relative size of the first and second lower molar crowns, and premolar crown and radicular anatomy) indicates attribution to Ardipithecus ramidus. The combined radioisotopic and palaeomagnetic data suggest an age of between 4.51 and 4.32 million years for the hominid finds at As Duma. Diverse sources of data (sedimentology, faunal composition, ecomorphological variables and stable carbon isotopic evidence from the palaeosols and fossil tooth enamel) indicate that the Early Pliocene As Duma sediments sample a moderate rainfall woodland and woodland/grassland., (C) 2005 Nature Publishing Group
Keywords: Africa; Animals; Ardipithecus ramidus; Biodiversity; Carbon; Chad; Dental Enamel; East Africa; Eastern Hemisphere; Endomorphological variables; Environment; Ethiopia; Faunal composition; Fossils; Geographical regions; Gona; Gona Wester Margin (GWM), Afar, Ethiopia; History, Ancient; Hominidae; Jaw; Kenya; Landforms; Miocene; Pan (ape); Pan troglodytes; Pliocene; Pliocene hominids; Poaceae; Radicular anatomy; Radioisotopes; Rain; Sedimentology; Sub-Saharan Africa; Time Factors; Tooth; Trees; Upper Miocene; World; Zanclea; Zanclean; article; carbon; chimpanzee; dept.ant; enamel; evolution; fauna; forest; fossil; grassland; hominid; molar tooth; paleoenvironment; premolar tooth; priority journal; rain; sedimentology